Peran Website Restoran terhadap Daya Tarik Konsumen Online - Yulianto, Budi; Dewi, Lusiana Citra; Wijaya, Oky (Bina Nusantara University, 2014)
Less-usability restaurant website will decrease its online sales. Restaurant website must easy to use and has good interface. The goals of the research are designing a restaurant website that can be online accessed by consumers and analyze its level of usability, interface, and multimedia elements. Outputs of the research are a restaurant website that delivers its information, place booking and delivery order facility, and location. Development methodology uses waterfall that contains system engineering, analysis, design, coding and testing, implementation, and maintenance. Conclusion of the research has shown that the developed website attracts online consumers, easily access to get information, good interface, and contains multimedia elements to supports restaurant in delivering newest product or information, as a good promotion tool that can be accessed 24 hours anytime and anywhere.